Classification of Polish cities based on environmental and communication conditions - Zaród, Jadwiga (Klasyfikacja polskich miast na podstawie warunków środowiskowych i komunikacyjnyc, 2020)
Problems associated with environmental pollution concern most large Polish cities. They are mainly caused by transport, municipal waste, emissions from the housing sector and from factories, particularly burdensome for the environment. Based on data related to the state and the protection of the natural environment and road transport, the author attempted to divide Polish cities with county (‘powiat’) rights into groups with different environmental features. Discriminatory analysis was used for the division. The highest average value of the discriminatory function was shown by the group with the most favourable environmental and social conditions. In subsequent groups, the environmental pollution grew more and more. In turn, classification functions of discriminatory analysis allowed for the assignment of individual cities to selected groups. Discriminatory analysis could therefore be used as a support tool for examining the state of the environment and environmental protection in cities with county rights. The goal of the work is to identify the diversity of environmental and communication conditions in Polish cities with county (‘powiat’) rights
Econometrics = Ekonometria, 2020, Vol. 24, No. 1, s. 12-22
Keywords: cities with county rights; environmental pollution; discriminatory analysis; analiza dyskryminacyjna; miasta na prawach powiatu; zanieczyszczenie środowiska